Active earth pressures from a log-spiral slip surface with arching effects. Issue 2 (17th May 2016) - Xie, Y.; Leshchinsky, B.
Abstract : The distribution of active earth pressures behind retaining structures is typically inferred from simplified Rankine or Coulomb analyses, both of which are triangular in shape and assume a planar slip surface. However, various experiments and numerical models have demonstrated an earth pressure distribution that is non-linear in shape, typically attributed to a phenomenon called 'soil arching'. Existing analytical solutions have typically evaluated arching with planar slip surfaces; however, slip surfaces that form behind retaining structures are often curvilinear, tending to follow a log-spiral shape, particularly when considering wall batter or interface friction between the backfill and wall. In this letter, the arching effect is considered using a log-spiral failure mechanism that has been developed by deriving a first-order differential equation and subsequently solved using a numerical approach. A series of charts are presented accounting for varying soil strengths, interface friction and wall batters.